DAMPAK KERJA LEMBUR SUAMI PADA PEMENUHAN NAFKAH BATIN ISTRI MASYARAKAT BATU LAYAR: ANALISIS HUKUM KELUARGA ISLAM BERBASIS STUDI KASUS - Goliz Cahyadi; Akhmad Husaini (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the impact of husbands’ overtime work on the fulfillment of wives’ emotional and spiritual needs (nafkah batin) from the perspective of Islamic family law, with a case study in Batu Layar Village, West Lombok Regency. The social dynamics in this tourism-based community show that the high frequency of overtime work affects the emotional harmony of families. Using a qualitative descriptive method, data were collected through field observation and in-depth interviews with seven respondents. The findings reveal that overtime work has a dual effect: it strengthens the family’s economic stability but reduces emotional attention, communication, and marital intimacy. From the standpoint of Islamic law, this situation constitutes taqsir (relative neglect) when the husband fails to maintain a balance between material and spiritual obligations, in accordance with the principle of mu‘āsyarah bil ma‘ruf (living together in kindness) in QS. An-Nisa’: 19. Indonesian positive law, through Law No. 1 of 1974 and the Compilation of Islamic Law, likewise obliges husbands to fulfill both material and spiritual needs proportionally. This research recommends religious and communicative solutions grounded in spiritual awareness to preserve marital harmony amid modern economic pressures